Regulamentação das apostas esportivas no Brasil: análise da lei n° 14.790/2023 - Oliveira, José Bruno Oliveira de (2024)
This article aims to analyze the main negative impacts of unregulated online sports betting, a scenario experienced by Brazilian bettors in recent years. This is a market that has grown enormously and generates billions of dollars, but which until now was surrounded by legal uncertainty and did not bring the State its due financial return. Based on this study, the legal measures that have been taken to resolve these problems are identified, with emphasis on the recent entry into force of Law 14.790/2023, which establishes the rules for the operation of the market and the way in which prizes and company revenue will be taxed, thus promoting a debate about the effects of the law as of 2024.